Meningkatkan Digital Savvy melalui Pembelajaran Berbasis IT pada Siswa Usia Sekolah Dasar di Desa Pogungjuru Tengah - Rintis Rizkia Pangestika; Sigit Dwiantoro; Nurul 'Aini; Muhammad Reza N. Khawatif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This training is one of Thematic Real Work Lectures (KKNT) activities as a form of non-profit higher education service to the surrounding community. The purpose of this activity is to train and improve information technology insight and knowledge (digital sense) skills of children from early childhood, especially from elementary school. Because the demands of life in the digital age are quick and practical. This activity was held from January to February 2023 for 60 elementary school students in grades 4, 5, and 6. The training takes place every Wednesday at 1:00 pm in his ICT lab room at SD Negeri Pogunjulu Tenga with KKNT student instructors (10 students in total). As a result of this activity, the students of Pogunjulu Tenga Primary School have become familiar with information technology, especially Microsoft Office.